EVALUATING SLOW RELEASE FERTILIZER PREPARED BY LOADING PHOSPHORUS ON SURFACE MODIFIED NANO SYRIAN ZEOLITIC TUFF - Salameh, B.; Habib, L. A.; Adra, A.; Hatem, Z. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to assessment of using nano Syrian zeolitic tuff (NSZT) as carrier to produce slow release phosphate fertilizer was executed. phosphate salt was loaded to modified nano-zeolite by HDTMA-Br (hexadecyl trimethyl ammonium bromide) surfactant application. Two main treatments (SMZ1, SMZ2), making approximately monolayer (83%) and bilayer (190%) real coverage of external cationic exchange capacity respectively. Phosphate was loaded on SMZ to prepare slow release fertilizer (SRF1, SRF2) respectively. Surface characteristics were conducted by using XRD and SEM techniques. Adsorption/ release experiments and incubation column were studied. Results showed that Langmuir isotherm was better to give good estimation of phosphorus sorption about nature of homogeneity. Phosphate release time into water solution from SRFs increased as surface modification ratio increased. Elovich model was good tool to predict the phosphate release ratio coefficient which was independent of HDTMA-Br modification coverage ratio. After 40 days of incubation experiment in columns, soil effect dropped up the leached phosphate in the flux less than 10% of the initial P loading concentration. Incubation column experiment confirms expectations about the anion exchange mechanism between phosphate and bilayer on NSZT.